Validation of the mobile wireless digital automatic blood pressure monitor using the cuff pressure oscillometric method, for clinical use and self-management, according to international protocols - Yoo, Sooyoung; Baek, Hyunyoung; Doh, Kibbeum; Jeong, Jiyeoun; Ahn, Soyeon; Oh, Il-Young; Kim, Kidong (Biomedical engineering letters, 2018)
The purpose of this study was to evaluate the accuracy of a mobile wireless digital automatic blood pressure monitor for clinical use and mobile health (mHealth). In this study, a manual sphygmomanometer and a digital blood pressure monitor were tested in 100 participants in a repetitive and sequential manner to measure blood pressure. The guidelines for measurement used the Korea Food & Drug Administration protocol, which reflects international standards, such as the American National Standard Institution/Association for the Advancement of Medical Instrumentation SP 10: 1992 and the British Hypertension Society protocol. Measurements were generally consistent across observers according to the measured mean ± SD, which ranged in 0.1 ± 2.6 mmHg for systolic blood pressure (SBP) and 0.5 ± 2.2 mmHg for diastolic blood pressure (DBP). For the device and the observer, the difference in average blood pressure (mean ± SD) was 2.3 ± 4.7 mmHg for SBP and 2.0 ± 4.2 mmHg for DBP. The SBP and DBP measured in this study showed accurate measurements that satisfied all criteria, including an average difference that did not exceed 5 mmHg and a standard deviation that did not exceed 8 mmHg. The mobile wireless digital blood pressure monitor has the potential for clinical use and managing one’s own health.